2015
DOI: 10.1242/jeb.119560
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen limited thermal tolerance is seen in a plastron breathing insect, and can be induced in a bimodal gas exchanger

Abstract: Thermal tolerance has been hypothesized to result from a mismatch between oxygen supply and demand. However, the generality of this hypothesis has been challenged by studies on various animal groups, including air-breathing adult insects. Recently, comparisons across taxa have suggested that differences in gas exchange mechanisms could reconcile the discrepancies found in previous studies. Here, we test this suggestion by comparing the behaviour of related insect taxa with different gas exchange mechanisms, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 47 publications
4
39
1
Order By: Relevance
“…For example, Verberk and Bilton (2011) showed that CT max estimates could be increased with oxygen supplementation or decreased by oxygen depletion in the stonefly Dinocras cephalotes. This finding was also observed (Verberk and Bilton, 2013) in four additional species, and further work (Verberk and Bilton, 2015) showed that in the air-breathing aquatic insect Ilyocoris cimicoides, hypoxic water did not influence heat tolerance, whereas hypoxic water reduced heat tolerance in a plastron (dissolved oxygen)-breathing Aphelocheirus aestivalis. To our knowledge, no studies in aquatic insects have previously explored whether oxygen limitation occurs at more ecologically relevant chronic thermal limits.…”
Section: Introductionsupporting
confidence: 66%
“…For example, Verberk and Bilton (2011) showed that CT max estimates could be increased with oxygen supplementation or decreased by oxygen depletion in the stonefly Dinocras cephalotes. This finding was also observed (Verberk and Bilton, 2013) in four additional species, and further work (Verberk and Bilton, 2015) showed that in the air-breathing aquatic insect Ilyocoris cimicoides, hypoxic water did not influence heat tolerance, whereas hypoxic water reduced heat tolerance in a plastron (dissolved oxygen)-breathing Aphelocheirus aestivalis. To our knowledge, no studies in aquatic insects have previously explored whether oxygen limitation occurs at more ecologically relevant chronic thermal limits.…”
Section: Introductionsupporting
confidence: 66%
“…By comparison, Thorpe and Crisp's data were 1.67 and 9.92 nmol s −1 g −1 , respectively, giving a scope of 5.9. A recent study of metabolic rate in inactive A. aestivalis at 5-15°C extrapolates to 2.62 nmol s −1 g −1 (=100 pmol s −1 ) at 20°C (Verberk and Bilton, 2015).…”
Section: Respiration Ratesmentioning
confidence: 94%
“…Conclusions about plastron function have been largely theoretical, although good measurements of plastron structure of the river bug Aphelocheirus aestivalis (Hinton, 1976) and rates of O 2 consumption have been measured for several species of plastron bugs (Kölsch and Krause, 2011;Thorpe and Crisp, 1949;Verberk and Bilton, 2015). According to a recent analysis (Seymour and Matthews, 2013), respiration rates of resting bugs range from 27 to 55% of the prediction of resting metabolic rates based on an interspecific allometric analysis of 391 species of insects in general (Chown et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature‐induced mismatches between oxygen‐delivery capacity and oxygen demand and the heat thresholds that bring a species to hypoxemic conditions have been suggested to underlie thermal tolerance limits in ectotherm species . Consequently, thermal specialists could be especially limited by their capacity to increase oxygen uptake to meet demand in warm conditions …”
Section: Respiration Of Eurytherms and Stenotherms: A Trade‐off Betwementioning
confidence: 99%